2022
DOI: 10.3389/fmicb.2022.942708
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Potential ESKAPE Surrogates for 222 and 254 nm Irradiation Experiments

Abstract: BackgroundDue to the increase in multidrug-resistant pathogens, it is important to investigate further antimicrobial options. In order not to have to work directly with pathogens, the investigation of possible surrogates is an important aspect. It is examined how suitable possible surrogate candidates for ESKAPE pathogens are for UVC applications. In addition, the inactivation sensitivities to 222 and 254 nm radiation are compared in relation.MethodsNon-pathogenic members (Enterococcus mundtii, Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Irradiation experiments have also been carried out on fruits such as apricots for pathogens such as salmonella. This shows that the decontamination method used has also been successfully applied to other bacteria and foodstuffs, especially fruits [15]. If one compares the fact that higher doses were required for 222 nm than for 254 nm to achieve the same reduction with other research projects, the results are confirmed.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Irradiation experiments have also been carried out on fruits such as apricots for pathogens such as salmonella. This shows that the decontamination method used has also been successfully applied to other bacteria and foodstuffs, especially fruits [15]. If one compares the fact that higher doses were required for 222 nm than for 254 nm to achieve the same reduction with other research projects, the results are confirmed.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast to the longer UV-C wavelengths, Far UV-C is less harmful to humans due to a lower penetration depth into the skin caused by absorption of the proteins of dead skin cells in the Stratum corneum [12]. For this reason, the question arises whether the irradiation of foods such as lamb's lettuce and chicory with UV-C and Far-UV-C radiation has a significant influence on the spread of pathogens, especially E. coli [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One can raise the question whether the assumption made above-S. carnosus and S. saprophyticus having comparable log reduction doses-is realistic, or if the non-pathogenic S. carnosus is possibly much more sensitive to UVA than, e.g., the pathogens S. saprophyticus or S. aureus. So far, there are no suitable studies on S. saprophyticus or S. aureus in the UVA range, but there are investigations for bacteria in solutions in adjacent spectral ranges at 222 nm (UVC), 254 nm (UVC), 405 nm (visible light) and 450 nm (visible light) [22,23]. At 222 nm, S. carnosus and S. aureus are equally photosensitive, at 254 nm, S. carnosus is more susceptible, and at 405 and 450 nm, S. aureus is more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The log-reduction doses of most pathogens are well below these threshold values. For example, Staphylococcus aureus, Pseudomonas aeruginosa , and severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) in solution require 222 nm irradiation doses of 3.4, 2.0, and 1.2 mJ/cm 2 , respectively, for 90% reduction [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%